Tumor Suppressor Cylindromatosis Acts as a Negative Regulator for Streptococcus pneumoniae-induced NFAT Signaling - Koga, Tomoaki (American Society for Biochemistry and Molecular Biology, 2008)
Gram-positive bacterium Streptococcus pneumoniae is an important human pathogen that colonizes the upper respiratory tract and is also the major cause of morbidity and mortality worldwide. S. pneumoniae causes invasive diseases such as pneumonia, meningitis, and otitis media. Despite the importance of pneumococcal diseases, little is known about the molecular mechanisms by which S. pneumoniae-induced inflammation is regulated, especially the negative regulatory mechanisms. Here we show that S. pneumoniae activates nuclear factor of activated T cells (NFAT) signaling pathway and the subsequent up-regulation of inflammatory mediators via a key pneumococcal virulence factor, pneumolysin. We also demonstrate that S. pneumoniae activates NFAT transcription factor independently of Toll-like receptors 2 and 4. Moreover, S. pneumoniae induces NFAT activation via both Ca(2+)-calcineurin and transforming growth factor-β-activated kinase 1 (TAK1)-mitogen-activated protein kinase kinase (MKK) 3/6-p38α/β-dependent signaling pathways. Interestingly, we found for the first time that tumor suppressor cylindromatosis (CYLD) acts as a negative regulator for S. pneumoniae-induced NFAT signaling pathway via a deubiquitination-dependent mechanism. Finally, we showed that CYLD interacts with and deubiquitinates TAK1 to negatively regulate the activation of the downstream MKK3/6-p38α/β pathway. Our studies thus bring new insights into the molecular pathogenesis of S. pneumoniae infections through the NFAT-dependent mechanism and further identify CYLD as a negative regulator for NFAT signaling, thereby opening up new therapeutic targets for these diseases.